Effects of drying temperature on iron and vitamin C retention of powdered malunggay (Moringa oleifera) leaves - Calzada, Ma. Abigail Enriquez
The effects of drying temperature on the iron and vitamin C retention, as well as color intensity, of powdered malunggay (Moringa oleifera) leaves were investigated.